Peningkatan Kualitas Biji Kakao Non Fermentasi Melalui Perlakuan Pendahuluan Sebelum Inkubasi - M. Iqbal Prawira Atmaja; Haryadi Haryadi; Supriyanto Supriyanto (Pusat Penelitian dan Pengembangan Perkebunan, 2016)
The cocoa beans produced by farmers in Indonesia are mostly nonfermented with unfavourable taste and flavour. Incubating the cocoa beans in acetate buffer medium has been shown to improve the quality of non fermented dried cocoa beans. Pre-incubation treatments of non fermented cocoa beans by physical treatments such as soaking and crushing them prior to the incubation in acetate buffer is expected to improve the beans quality (i.e. fermentation index and polyphenol). The aim of the research was to determine the effect of pre-incubation treatment of non fermented dried cocoa beans in acetate buffer medium on fermentation index and total polyphenols content.The research was carried out in Process Engineering Laboratory, Food Chemical and Biochemical Laboratory, and Postharvest Technology Laboratory at Gadjah MadaUniversity from April to December 2013. The research used three treatments, first: the crushed beans size 4 mm, whole beans soaked in water (45°C; 16 hours), and beans without soaking (control). The incubation was performed in two stages, the first stage was in the acetate buffer medium at pH 2.7; 600 mM for 24 hours, then subconsequently at pH 5.5; 600 mM for 12 hours. The results showed that crushed bean treatment of non fermented cocoa beans prior to incubation increased the fermentation index values, from 1.15 to1.54 and decreased total polyphenol content from 55.69 to 24.16mg GAE/g.